Simulation and optimization of a silicon-polymer bimorph microgripper - Phu, Phan Huu; Viet, Nguyen Ngoc; Ngoc, Nguyen Minh; Hung, Vu Ngoc; Trinh, Chu Duc (Vietnam Journal of Mechanics, 2012)
This paper presents an electro-thermally bimorph microgripper based on silicon-polymer laterally stacked structures and a method to optimized the fabricated device. The actuated displacement is enhanced due to the polymer constraint effect. Both the thermal expansion and apparent Young’s modulus of the constrained polymer blocks are significantly improved, compared with the no constraint one. The device consists of a serpentine-shape deep silicon structure with a thin film aluminum heater on the top and filling polymer in the trenches among the vertical silicon parts. The fabricated bimorph microgripper can operate in four modes and generates a large motion up to 15 μm. The simulated results are met the fabricated measurements. An optimized structure is proposed for decreasing the working temperature, power consumption but increasing the output displacement. The simulated results are showed that the output displacement is increased up to 550% and temperature profile improved considerably. This electro-thermally silicon-polymer opened and closed microgripper can be used in micro-robotics, micro-assembly, minimally invasive surgery, living cells surgery.